Իրանի նախաիսլամական շրջանի գրականության նմուշները բովանդակող ձեռագրերը Մատենադարանում - Կոստիկյան, Քրիստինե; Մեհդի Բաղի («Նաիրի» հրատ.)
Mihrdat Tiryakyan, a poet who translated parts of Firdausi‘s Shahnameh, generously donated two Persian manuscripts (Arabic Script Collection, ms. 1018, 1611) to Matenadaran in 1963 and 1972, as well as three manuscripts containing parts in Pahlavi and Avestan (Non-Armenian Manuscript Collection, ms. 125, 129, 130) in 1970. The manuscripts used to belong to the donor‘s father Harutyun Tiryakyan, an outstanding physician and philologist, who was interested in the comparative linguistics of Persian and Armenian, and published works on the subject. In addition to translating Firdausi and Saadi, H. Tiryakyan also translated historical and didactic works in Pahlavi. While most of his translations and research were published during his lifetime, his son Mihrdat continued the efforts after his death. A considerable part of H. Tiryakyan‘s personal archive currently residing in the Charentz Museum of Literature and Art, as well as the aforementioned manuscripts, refer to his time in Persia (from 1896 to 1906), during which he served as the chief physician of the Shah‘s harem, his scientific research in comparative linguistics, his translations from Middle and New Persian, as well as his close ties with the high officials of the Qajar government and the Zoroastrian community of Iran. The article describes the manuscripts donated to Matenadaran by M. Tiryakyan that contain works in New Persian, Middle Persian and Avestan.
Keywords: Ձեռագրագիտություն; Գրականություն